Learning disability and leadership: Becoming an effective leader. (10th September 2013) - Luria, Gil; Kalish, Yuval; Weinstein, Miriam
Summary This study investigates learning disability (LD) as an individual‐differences variable predicting leadership emergence, role occupancy, and effectiveness. We hypothesize that individuals with LD are less likely to occupy leadership roles, and that informal group processes (leadership emergence) will mediate the relationship between LD and leadership role occupancy. We also hypothesized that, among leaders promoted and selected for leadership training, there would be a negative relationship between LD and effective leadership. We first checked for LD in a sample of 1076 soldiers, measuring cognitive ability with a geometric‐analogies test as a control. Some months later, during the soldiers' basic training, we measured leadership emergence. We then identified those who were selected for leadership training, recording, and measuring their effectiveness according to supervisory and peer evaluations. Leadership emergence was found to mediate the negative relationship between LD and leadership role occupancy. There were no significant differences among leaders (n = 308) with and without LD in regard to leadership effectiveness. Copyright © 2013 John Wiley & Sons, Ltd.